2014
DOI: 10.1177/1359105314540965
|View full text |Cite
|
Sign up to set email alerts
|

Predicting post-traumatic stress and health anxiety following a venous thrombotic embolism

Abstract: This research identified psychosocial factors associated with post-traumatic stress and health anxiety following a venous thrombotic embolism. In all, 158 participants, largely registered with a venous thrombotic embolism information website (Lifeblood: The Thrombosis Charity), completed an online survey. Post-traumatic symptom scores were linked to health threat, and not moderated by perceived control over risk for further venous thrombotic embolism. Health anxiety was associated with continuing symptoms and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 21 publications
9
43
0
Order By: Relevance
“…This study examined the experience of people in the months immediately following a VTE, and the impact it had on them and their life. Its findings support those of earlier studies in less representative samples (Bennett et al ., ; Noble et al ., ), which found high levels of trauma, health anxiety, and PTSD symptoms within this patient population. Key themes identified suggested the experience of VTE, its treatment, and uncertain future each contributed to a life‐changing experience, risk for high levels of distress, and the paradoxical experience of post‐traumatic growth and more positive life benefits.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…This study examined the experience of people in the months immediately following a VTE, and the impact it had on them and their life. Its findings support those of earlier studies in less representative samples (Bennett et al ., ; Noble et al ., ), which found high levels of trauma, health anxiety, and PTSD symptoms within this patient population. Key themes identified suggested the experience of VTE, its treatment, and uncertain future each contributed to a life‐changing experience, risk for high levels of distress, and the paradoxical experience of post‐traumatic growth and more positive life benefits.…”
Section: Discussionmentioning
confidence: 98%
“…Lack of information from health care professionals also reinforced uncertainties further and led to the increased use of primary health care resources, often as a means of both information provision and reassurance. These features of post‐VTE anxiety may contribute to the high levels of psychological distress reported here and in early studies (Bennett et al ., ;).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 This relatively low frequency of CTEPH may be the reason for the limited number of studies focusing on HRQoL and the psychological well-being of patients with PE. [4][5][6][7][8][9] It has been suggested that CTEPH itself is the extreme manifestation of a much more common phenomenon of permanent changes in pulmonary haemodynamics, cardiac function and pulmonary gas exchange after acute PE, which is associated with dyspnoea and decreased exercise capacity. Additionally, several studies have shown that up to 50% of the patients with a history of PE report persistent dyspnoea a long time after PE.…”
Section: Introductionmentioning
confidence: 99%